2013
DOI: 10.3109/13668250.2013.772956
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual abilities of children with mild intellectual disability: Analysis of Wisconsin Card Sorting Test performance

Abstract: We can conclude that there is a significant progress of conceptual abilities between the age of 13 years to 13 years 11 months, compared to other assessed age groups. The results of our research suggests that the development of mental set flexibility is the basis of progress in conceptual abilities, thus intervention programs should offer specially designed activities that vary in their attentional demands, content, conceptual patterns, and actions required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Also, children with ID made the same mistakes as much younger typically developing children (Goharpey, Crewther & Crewther, 2013). Bearing in mind that the appropriate strategic behavior is associated with the ability to evaluate demands and contexts, and with the ability to control, monitor and flexibly apply previously acquired strategies in new situations, limited spontaneous usage and transfer of strategies may be the result of limitations in basic executive functions, inhibitory control, working memory, and cognitive flexibility (Dermitzaki, Stavroussi, Bandi & Nisiotou, 2008;Gligorović & Buha, 2013b). A planning strategy requires keeping relevant information, inhibiting the activities which initially seem logical but do not lead to the ultimate goal, and flexibly selecting and varying different stages of a task.…”
Section: Gligorović M Buha N: Influence Of Inhibitory Control Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, children with ID made the same mistakes as much younger typically developing children (Goharpey, Crewther & Crewther, 2013). Bearing in mind that the appropriate strategic behavior is associated with the ability to evaluate demands and contexts, and with the ability to control, monitor and flexibly apply previously acquired strategies in new situations, limited spontaneous usage and transfer of strategies may be the result of limitations in basic executive functions, inhibitory control, working memory, and cognitive flexibility (Dermitzaki, Stavroussi, Bandi & Nisiotou, 2008;Gligorović & Buha, 2013b). A planning strategy requires keeping relevant information, inhibiting the activities which initially seem logical but do not lead to the ultimate goal, and flexibly selecting and varying different stages of a task.…”
Section: Gligorović M Buha N: Influence Of Inhibitory Control Onmentioning
confidence: 99%
“…A planning strategy requires keeping relevant information, inhibiting the activities which initially seem logical but do not lead to the ultimate goal, and flexibly selecting and varying different stages of a task. Our previous studies determined that 10-14 year-old children with mild intellectual disability (MID) had difficulties in solving verbal and non-verbal problems (Buha & Gligorović, 2012;Gligorović & Buha 2013b). By applying Tower of London (ToL) test, aimed at assessing the ability to solve non-verbal problems, it was determined that children with MID were characterized by the so called unstable (wavering) approach to a problem, which involves alternating perceptive strategies and higher order strategies.…”
Section: Gligorović M Buha N: Influence Of Inhibitory Control Onmentioning
confidence: 99%
“…Classification is an explicit learning process driven by forming hypotheses about discrete categories (e.g., color, shape, and size). This capacity depends on executive functioning (Gligorovic & Buha, 2013;Phillips et al, 2014;Robles-Bello et al, 2018). The PreCL results suggest that the capacity for rule-based categorization in preschoolers with ID (DS, NSID) is lower than that of controls with a similar chronological age.…”
Section: Rule-based Categorizationmentioning
confidence: 90%
“…The beta weight in the snake delay task (response inhibition) was negative in typically developing children, positive in children with DS, and positive for both groups on the pony/gator task (interference control) (see Table 1). Gligorovic and Buha (2013) found that when engaging in rulebased categorization, children's ability to create conceptual patterns and replace one conceptual representation for another (mental set rigidity) is altered in NSID. The high rate of perseverative errors suggests deficits in substituting one set for another, even when the children correctly frame their mental set.…”
Section: Rule-based Categorizationmentioning
confidence: 98%
See 1 more Smart Citation